2016
DOI: 10.1111/bju.13361
|View full text |Cite
|
Sign up to set email alerts
|

Phytotherapeutic interventions in the management of biochemically recurrent prostate cancer: a systematic review of randomised trials

Abstract: ObjectiveTo evaluate the evidence from randomised trials for the efficacy and safety of phytotherapeutic interventions in the management of biochemically recurrent (BCR) prostate cancer, indicated by prostate-specific antigen (PSA) progression, numbers progressing to/time to initiation of androgen-deprivation therapy or salvage therapy. Patients and MethodsMEDLINE (Ovid), EMBASE (Ovid), AMED (Ovid), CINAHL (EBSCO) and the Cochrane Library databases were searched. Clinical trials investigating phytotherapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 49 publications
(124 reference statements)
0
18
0
1
Order By: Relevance
“…There are a number of recently published clinical trials and metaanalysis data revealing beneficial health effects of lycopene (Cicero & Colletti, 2015;Mahmoodnia, Mohammadi, & Masumi, 2017;Singh & Bagewadi, 2017;van Die et al, 2016). However, only few of them (Graff et al, 2017;Zhu, Gertz, Cai, & Burri, 2016) adequately address the issue of lycopene bioavailability in volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of recently published clinical trials and metaanalysis data revealing beneficial health effects of lycopene (Cicero & Colletti, 2015;Mahmoodnia, Mohammadi, & Masumi, 2017;Singh & Bagewadi, 2017;van Die et al, 2016). However, only few of them (Graff et al, 2017;Zhu, Gertz, Cai, & Burri, 2016) adequately address the issue of lycopene bioavailability in volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Integrative care includes complementary and alternative methods, alongside traditional medical approaches. The effectiveness of this approach is being studied in addressing pain management and treating PTSD among veterans (35,37), symptom management among cancer patients (38), and supporting healthy behaviors such as smoking cessation (39) and weight loss (40). Given our finding that baby boomers are more likely than pre-boomers to try CAM modalities such as energy healing, herbal therapies, massage, and relaxation or meditation techniques, a continuing focus on integrative care is important.…”
Section: Resultsmentioning
confidence: 99%
“…Overall there is a dearth of high quality studies that can provide guidance regarding the anti-cancer use of the isolated compounds/parental extracts/combination of compounds. A recent review of the literature for clinical trials that investigated phytochemical intervention in biochemically recurrent prostate cancer identified 23 full-length articles of which only 2 studies that were identified as having placebo-controlled, 2 were active control studies and one was a dose-response study [131]. Using the US Food and Drug Administration model these compounds must be evaluated for anti-cancer surrogate markers (identified and validated from cell culture models) or endpoints to establish risk reduction.…”
Section: Future Directionsmentioning
confidence: 99%